ELEVATING LONG-TERM ELDERLY CARE IN MALAYSIA: A CLUSTER ANALYSIS APPROACH BASED ON BENCHMARKING WITH SELECTED COUNTRIES - Noorlianni Rosli; Syazreen Nisa Shair; Shamshimah Samsudin, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
Malaysia is expected to become an aged society with a 14.1% ageing ratio in 2039, boosting demand for Long-Term Care (LTC). Nonetheless, a thorough review of current LTC systems is crucial due to their complexity, encompassing numerous ministries and departments. In analysing LTC systems in various countries based on components of effective LTC systems, this research suggests a new LTC framework for Malaysian systems. Cluster analysis is used across benchmarked nations: Australia, Germany, Japan, Singapore, Thailand, the United Kingdom, and the United States of America. There are two typologies used, with a total of ten variables employed: a) organisational depth with seven variables: legal framework, policy objectives, policy approach, means-tested assessment, entitlements, cash benefits, and choice of care provider; b) financial generosity and sustainability with three variables: financing mechanism, cost-sharing, and LTC expenses. Four key takeaways from the benchmarked countries: a) LTC insurance scheme, as adopted in Germany and Japan, proves effective with universal coverage, greater disclosure, and a structured approach; b) community-based model, widely adopted across all countries, fosters active stakeholders engagement in meeting elderly’s needs; c) Centralised Administration (CA) provides a structured avenue to manage LTC services and expenses; and d) cost-sharing via private-public arrangements ensures the sustainability of the LTC expenses. The study suggests five improvements for effective LTC systems: a) broaden the recipients’ pool to include the bottom 40% of the population to accommodate their financial constraints; b) implement a robust means-tested evaluation for equity, transparency, and inclusivity; c) incorporate a community-based model for comprehensive coverage; d) create a CA to handle complexity; and e) use public-private partnerships for sustainable financing model. In summary, this study aids policymakers in tackling the intricacies of Malaysia’s LTC systems in line with the intended policy goals of guaranteeing a healthy ageing population, advocating comprehensive protection, and stimulating community-based care.